Comparison of static and dynamic balance parameters and some performance characteristics in rock climbers of different levels - Tolga Aksıt; Gamze Cırık (Türk Spor ve Egzersiz Dergisi)
The aim of the present study was to compare anthropometric characteristics, dynamic balance and physical performances of climbers at recreational and intermediate levels. Climbers were seperated in two groups according to climbing difficulty levels.  A total of 24 male rock climbers; 16 at beginner level (mean ± sd; 26.2 ± 4.2 years, climbing grade; 6a/6a+ ) and 8 intermediate level (mean ± sd; 30.8 ± 4.9 years, climbing grade; 7c/7c+)  participated voluntariliy in the study Measurements were taken from both groups for anthropometric (body height, weight, body fat ratio, skinfolds, humerus breadth, arm span), intermittent finger hang (IFH), bent-arm hang and hand grip strength. Static (open/closed eyes) and dynamic balance was measured with isokinetic balance test on a force platform. Differences between groups were calculated using an independent samples t-test and also Mann-Whitney U test was used for nonparametric values. As a result, advance group has significantly greater values for limits of stability, humerus breadth, ape index and IFH (p lt;0.05). No significant difference was found between groups for the other balance parameters, anthropometric characteristics and climbing performance factors. In consequence, static balance parameters of rock climbers were found to be similar to those of other elite athletes in the literature. On the other hand, dynamic balance could be considered to be a more important parameter than static balance for climbers by the nature of the sport.